Alcoholism and Judgments of Affective Stimuli - Clark, Uraina S. (2007)
This study sought to differentiate alcoholism-related changes in judgments of emotional stimuli from those of other populations in which such changes have been documented. Two sets of visual stimuli, one containing words and the other containing drawings of faces (representing a range of emotional content), were presented to abstinent alcoholic adults with and without Korsakoff’s syndrome, as well as to a healthy control group and four groups of patients with other neurobehavioral disorders: Parkinson’s disease, schizophrenia, depression, and posttraumatic stress disorder. Participants rated the stimuli according to emotional valence and intensity of emotion. Results implicated bi-hemispheric frontal and subcortical involvement in the abnormalities of emotion identification associated with alcoholism, and they also support the notion of age-related vulnerabilities in conjunction with alcoholism.